The role of Sc on the microstructures and mechanical properties of the Ni-rich NiTi alloy. (June 2022) - Li, B.; Zhang, F.X.; Zheng, L.J.; Zhang, H.
Abstract: The microstructure and mechanical properties of Ni-rich alloys with the addition of Sc range from 0.15 at% to 0.5 at% were investigated by X-ray diffractometer(XRD), electro-probe microanalyzer(EPMA), transmission electron microscopy(TEM), microhardness, room-temperature tensile properties, and room-temperature fracture toughness in this paper. The as-cast binary alloy and Sc modified ternary alloy are mainly composed of NiTi matrix phase, Ni4 Ti3, and Ni3 Ti2 phases. After solution treatment, the Ni3 Ti2 phase is dissolved back into the matrix, and the alloy mainly consists of NiTi matrix phase and nanoscale Ni4 Ti3 phases. The addition of Sc inhibits the precipitation of brittle Ti2 Ni phases because O is prone to combine with Sc to form Sc2 O3 . Trace Sc addition has a weak effect on the microhardness, and it can improve the room-temperature tensile properties and fracture toughness of the alloy. Trace Sc addition moderately reduce the size of the Ni4 Ti3 phases and change the aspect ratio of the Ni4 Ti3 phases. The reduced precipitate size is responsible for the improvement of alloy mechanical properties. Graphical Abstract: ga1 Highlights: Sc combines with O to form Sc2 O3, suppressing the formation of the Ti2 Ni phase. Trace addition of Sc can improve tensile properties and fracture toughness. Trace addition of Sc does not change the type of precipitates. Trace addition of Sc moderately reduces the size of the Ni4 Ti3 phases. Trace addition of Sc changes the aspect ratio of the Ni4 Ti3 phases.